The Influence of the RADEC Learning Model on Critical Reading Ability of PGSD Students - Musliha, Neni Nadiroti; Nuriyanti, Risma; Asy’ari, Lutfi; Mutiara, Laras (Universitas Sebelas Maret, 2024)
This research was motivated by the low level of critical reading of PGSD students during direct learning activities. The aim of this research is to see the influence of the RADEC learning model on critical reading of PGSD students. The research method used is a quantitative method with a pre-experimental one group pretest posttest design with a sample size of 20 PGSD students. The research instruments used were questionnaires and observation sheets to see students' critical reading abilities.The research results showed that the critical reading scores during the pretest of 20 students were in the moderate category, totaling 8 people with a percentage of 40%, the low category totaling 10 people with a percentage of 50%, and the very low category totaling 2 people with a percentage of 10%. At the time of the posttest, 20 students experienced significant changes, namely 14 people were in the very high category with a percentage of 70%, 3 people in the high category with a percentage of 15%, and 3 people in the moderate category with a percentage of 15%. So it can be concluded that the RADEC learning model influences the critical reading of PGSD students.